2017
DOI: 10.2139/ssrn.2906221
|View full text |Cite
|
Sign up to set email alerts
|

Austerity, Inequality, and Private Debt Overhang

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…How each household's welfare is affected depends on her position in the financial market. By the same token, and related to the current austerity debate, our results point towards important welfare effects of fiscal consolidations that could harm the less financially well-off part of the population, in line with the results obtained by Klein and Winkler (2017).…”
Section: Welfare Effectssupporting
confidence: 90%
See 1 more Smart Citation
“…How each household's welfare is affected depends on her position in the financial market. By the same token, and related to the current austerity debate, our results point towards important welfare effects of fiscal consolidations that could harm the less financially well-off part of the population, in line with the results obtained by Klein and Winkler (2017).…”
Section: Welfare Effectssupporting
confidence: 90%
“…Agnello and Sousa (2014) find that spending-driven fiscal adjustments deteriorate income distribution, whereas in Klein and Winkler (2017), austerity leads to a strong and persistent increase in income inequality only in periods of private debt overhang. DeGiorgi and Gambetti (2012) find that after a government spending shock consumption increases at the bottom of the consumption distribution but falls at the top, implying a reduction of consumption inequality.…”
mentioning
confidence: 99%
“…Additionally,Klein and Winkler (2017) provide empirical evidence supporting the view that fiscal consolidations lead to a strong and persistent increase in income inequality during periods of private debt overhang. 14 For example, it is well documented that in the U.S. during the financial crisis, the households that took subprime loans were much more prone to foreclosure and bankruptcy(Li and White, 2009).…”
mentioning
confidence: 58%
“…The literature on this topic is still scarce, but not non-existent. One strand of the literature has focused on the relationship between the different forms of debt.Angeletos et al (2016) highlighted that government debt expansions significantly influence households' financial condition; investigating the impact of government debt on corporate financing decisions,Demirci et al (2017) found a negative relation between government debt and corporate leverage using data on 40 countries during the 1990-2014 period; and Uusküla (2016) examined the relationship between more than 30 macroeconomic variables and debt-to-GDP ratios for household, nonfinancial corporation and aggregate debt in a panel of European Union countries.Another strand of literature examines the effects that the generalized and necessary deleveraging process currently taking place in the private sector may have on economic activity [seeCrowe et al (2011),Ruscher and Wolff (2013),Cuerpo et al (2015) orKuvshinov et al (2016)]. Other authors (see, e. g.,Bernardini and Peersman, 2015;Klein, 2016) have shown that the effects of fiscal consolidations crucially depend on the level of private indebtedness (mostly household leveraging), whereas the state of the business cycle and the level of public debt play only a minor role in the effectiveness of fiscal policy 13 .…”
mentioning
confidence: 99%
“…. 13 Additionally, Klein and Winkler (2017) provide empirical evidence supporting the view that fiscal consolidations lead to a strong and persistent increase in income inequality during periods of private debt overhang. 14 For example, it is well documented that in the U.S. during the financial crisis, the households that took subprime loans were much more prone to foreclosure and bankruptcy (Li and White, 2009).…”
mentioning
confidence: 83%